Achieving High Flotation Recoveries from Browns Polymetallic Ore - G Hayes (The Australasian Institute of Mining and Metallurgy, 2002)
Ore from the Browns deposit near Batchelor, in the Northern Territory of Australia, is a fine-grained polymetallic sulfide ore hosted in graphitic black shale. Minerals of economic significance are seigenite (Co,Ni)4S3, Galena (PbS) and Chalcopyrite (CuFeS2) with minor Sphalerite (ZnS). Gangue minerals include quartz, carbon and K-feldspar. The grain size is fine, with a significant amount of the seigenite present as Early flotation work determined that a grind size of around 20 microns was required to achieve clean sulfide concentrates. This work recommended oil agglomeration flotation, in which small sulfide minerals were collected, then loosely agglomerated with oil ahead of flotation into a heavily mineralised froth. In the 400 kg/hr prototype plant this froth proved unmanageable. A conventional flotation circuit after grinding to a P80 of 24 microns and using very low flotation pulp densities resulted in an 86 per cent cobalt recovery.The paper analyses further laboratory work which has increased cobalt recovery to 91 per cent by grinding to û250 microns ahead of flash flotation. The real cobalt recovery breakthrough comes from flash flotation of the whole mill discharge rather than the more usual flash flotation of cyclone underflow. Flash flotation tailings are ground to û38 microns and are floated under normal flotation conditions with only the scavenger concentrates being reground to 20 microns.A one tonne per hour prototyping campaign is scheduled to demonstrate the robustness of this circuit.